2008
DOI: 10.1007/s00792-008-0178-2
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial ice-binding protein from the Vostok ice core

Abstract: Bacterial and yeast isolates recovered from a deep Antarctic ice core were screened for proteins with ice-binding activity, an indicator of adaptation to icy environments. A bacterial strain recovered from glacial ice at a depth of 3,519 m, just above the accreted ice from Subglacial Lake Vostok, was found to produce a 54 kDa ice-binding protein (GenBank EU694412) that is similar to ice-binding proteins previously found in sea ice diatoms, a snow mold, and a sea ice bacterium. The protein has the ability to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 24 publications
5
95
0
Order By: Relevance
“…Greenland, Antarctica, glaciers) is formed largely from precipitation, and this may be triggered by PBAP in some situations (Sands et al, 1982;Christner et al, 2008b;Po¨schl et al, 2010). Bacteria have been discovered in ice cores from Antarctica at depths up to 3519 m (Raymond et al, 2008), giving possible evidence to the idea that these organisms have been introduced through precipitation. Thus, surface snow under windblown conditions could be a powerful source for PBAP via resuspension (Pomeroy and Jones, 1996).…”
Section: Definition and Sources Of Primary Biological Aerosol Particlesmentioning
confidence: 99%
“…Greenland, Antarctica, glaciers) is formed largely from precipitation, and this may be triggered by PBAP in some situations (Sands et al, 1982;Christner et al, 2008b;Po¨schl et al, 2010). Bacteria have been discovered in ice cores from Antarctica at depths up to 3519 m (Raymond et al, 2008), giving possible evidence to the idea that these organisms have been introduced through precipitation. Thus, surface snow under windblown conditions could be a powerful source for PBAP via resuspension (Pomeroy and Jones, 1996).…”
Section: Definition and Sources Of Primary Biological Aerosol Particlesmentioning
confidence: 99%
“…Although their work came up short after a long and exhaustive search, Scholander et al did show that the fish prevented freezing by using antifreeze that must be highly unusual. Therefore, the studies described in this publication set the stage for the insightful and innovative work of DeVries that in turn, lead us to today (Duman and Olsen, 1993;Zongchao and Davies, 2002;Griffith and Yaish, 2004;DeVries, 2005;Raymond et al, 2008;Duman et al, 2010) where the many varied antifreeze proteins that have been identified in numerous species of animals, plants, fungi, bacteria, etc., continue to be studied by multiple laboratories around the world.…”
Section: Classicsmentioning
confidence: 98%
“…For example, a question of great interest is origin and fate of the Lake Vostok, stayed buried under thick ice shield in Antarctic for more than 500 000 years [1;2]. In recent years, psychrophilic microflora from Vostok and other sub-glacial lakes in Antarctica have been the focus of increasing attention from both basic science and biotechnology perspectives, but the main obstacle for such lake's exploration is the danger of their contamination during sampling process [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%